Dual-mode 3D printed dynamic wrist driven orthosis for hand therapy exercises - Risangtuni, Ayu Gareta; Suprijanto, S.; Nazaruddin, Yul Yunazwin; Mahyuddin, Andi I. (Frontiers in Mechanical Engineering, 2023)
The primary objective of the Dual-mode Dynamic Wrist Driven Orthosis (D-WDO) is to facilitate wrist-hand therapy exercises for patients with varying levels of residual muscle function. This dualmode D-WDO system comprises two main components: the orthosis structure and the soft pneumatic actuator (SPA). All system components were designed and produced using Computer Aided Design (CAD) software and the Fused Deposition Modeling (FDM) 3D printing technique. The D-WDO's structure is constructed from PLA (Polylactic Acid), while the SPA is made from TPU (Thermoplastic Polyurethane) filament. The D-WDO can be operated in passive or active mode by attaching or detaching the SPA from the structure. This D-WDO system is particularly suitable for patients with a minimum MMT level between 2 and 3, as it provides assistance for wrist movement and supports repetitive wrist motion to enhance wrist muscle function. However, it's important to note that the operation and performance of the dual-mode D-WDO system may vary depending on the chosen system configuration. The active D-WDO's performance demonstrates its ability to achieve the necessary wrist flexion angle for a functional wrist joint, especially in the context of daily activities.